Corpos negros docentes: identificando trajetórias e experiências no Instituto Federal de Minas Gerais - Márcia Basília de Araújo (2020)
This research aims at analyzing the trajectory, presence and practices of black teachers at the Federal Institute of Minas Gerais - IFMG (Brazil), and the consequent repercussion on its faculty. IFMG is a multicampus college, whose rectory is located in Belo Horizonte and other the campuses are spread over several cities in Minas Gerais. Being a teacher at IFMG presupposes working with the dimensions Teaching, Research and Extension in an institution that offers basic, technical and technological education, with work, science, culture and technology as axes. Three research instruments were considered: identification form sent to all the faculty, resumé (available on Platform Lattes); and the episodic narrative interview method (FLICK, 2009). Sixteen subjects were interviewed in April and August 2018, based on the following generating question: “Tell me a little about how you arrived at IFMG, where you came from and what you brought to this institution”. The concept of identity was worked from the perspectives of Hall (2005), Woodward (2009), Novaes (1993), Fanon (2008) and Bhabha (2013). Black identity was analyzed in the light of Gomes (2003,2017), Hall (1987), Fanon (2008), Munanga (2003) and Carneiro (2005). At times, it was necessary to use the concept of intersectionality based on Akotirene (2018) and Crenshaw (2012). In order to understand the life trajectories of the interviewed teachers, the concepts of hardship (pruebas) and support (soportes) coined by Danilo Martuccelli (2007) and also worked by Katya Araújo (2010) proved to be especially important. Two other concepts that appeared considerably during the analyses were those of racial democracy (Hasenbalg, 1979; Jesus, no prelo) and whiteness (Shucman, 2014; Gomes & Miranda, 2009). The research showed that the number of black teachers at IFMG is lower than that of whites, although blacks are represented in a higher percentage than that of universities; that the various manifestations of racism were present as hardship in the lives of most of the subjects interviewed; that the support mobilized by the subjects is found in many arenas such as family, school, and work; and that black teachers are engaged in teaching, research, extension and management activities. According to the results, increasing insertion in research and extension activities is still a challenge, especially due to the specifity of the Institute organization, that demands a great deal of time for teaching activities and is reactive when dealing with ethnic-racial relations and propositional when dealing with research and extension. Results emphasize a higher participation rate of black teachers in the production and dissemination of knowledge committed to human life, local development and the strengthening of local productive arrangements than in the strengthening of large-scale production.